2016
DOI: 10.1186/s12883-016-0740-y
|View full text |Cite
|
Sign up to set email alerts
|

Is upper limb virtual reality training more intensive than conventional training for patients in the subacute phase after stroke? An analysis of treatment intensity and content

Abstract: BackgroundVirtual reality (VR) training is thought to improve upper limb (UL) motor function after stroke when utilizing intensive training with many repetitions. The purpose of this study was to compare intensity and content of a VR training intervention to a conventional task-oriented intervention (CT).MethodsA random sample of 50 video recordings was analyzed of patients with a broad range of UL motor impairments (mean age 61y, 22 women). Patients took part in the VIRTUES trial and were randomized to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 34 publications
5
40
0
2
Order By: Relevance
“…In general, authors reported an overall median of 570 min of VR (or computer games) therapy delivered, with duration ranging from 20 to 60 min per session, and 8 to 36 sessions [ 24 ]. Otherwise, intensity of training is rarely reported for VR training (see [ 25 ] for an exception). However, this is a critical factor to estimate cost-effectiveness of VR-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, authors reported an overall median of 570 min of VR (or computer games) therapy delivered, with duration ranging from 20 to 60 min per session, and 8 to 36 sessions [ 24 ]. Otherwise, intensity of training is rarely reported for VR training (see [ 25 ] for an exception). However, this is a critical factor to estimate cost-effectiveness of VR-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity of training is important. While more action is reported to take place on virtual reality rehabilitation than in conventional therapy in general [34], authors reported an overall median of 570 min of VR (or computer games) therapy delivered, with duration ranging from 20 to 60 minutes per session, and 8 to 36 sessions [35]. Our study has totaled 240 minutes of training over 12 sessions (mainly correlated to the usual length of stay in our service).…”
Section: Discussionmentioning
confidence: 76%
“…The features of the game for motor rehabilitation, such as diversity of game, variety of artificial environment or stimulation, can improve interest and motivation long‐term to help maintain repetitive intervention. Also, visuo‐auditory feedback provided through the game is an important challenge to promote cognitive effort and work performance, thereby enhancing cortical plasticity by motor learning . Several studies have shown that not only the effect of the game‐based intervention, but also providing an opportunity for appropriate performance training in consideration of safety, cost and time for the user, plays a role in the enhancement of motor function .…”
Section: Discussionmentioning
confidence: 99%